2022
DOI: 10.1101/2022.11.03.514759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Target-distractor competition modulates saccade trajectories in space and object-space

Abstract: Saccade planning and execution can be affected by a multitude of factors present in a target selection task. Recent studies have shown that the similarity between a target and nearby distractors affects the curvature of saccade trajectories, due to target-distractor competition. To further understand the nature of this competition, we varied the distance between and the similarity of complex target and distractor objects in a delayed match-to-sample task to examine their effects on saccade trajectories and bet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Saccades executed at short processing times displayed a strong bias for selecting objects closer to fixation (less eccentric). Additionally, the trajectory shifts of these saccades towards the distractor were consistent with weighted vector averaging, as has been previously reported for saccade deviations towards distracting objects [10][13][29] [30][31][32] . Our results for both the saccade trajectories and accuracy suggest that the weight of each object decreases linearly as its eccentricity increases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Saccades executed at short processing times displayed a strong bias for selecting objects closer to fixation (less eccentric). Additionally, the trajectory shifts of these saccades towards the distractor were consistent with weighted vector averaging, as has been previously reported for saccade deviations towards distracting objects [10][13][29] [30][31][32] . Our results for both the saccade trajectories and accuracy suggest that the weight of each object decreases linearly as its eccentricity increases.…”
Section: Discussionsupporting
confidence: 87%
“…Processing Time Division: Following Giuricich and colleagues [10] , trajectory metrics were used to separate saccadic responses made between active and completed decision making stages. The short processing time range was determined by saccade latencies with significant deviations towards the distractor, while the long processing time range was determined by saccade latencies with significant deviations away from the distractor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the hypothesis that the mechanisms responsible for deploying spatial attention and those involved in programming saccades are essentially the same (i.e., the premotor theory of attention; Rizzolatti et al, 1987; Belopolsky and Theeuwes, 2012). However, later studies showed that attention effects on saccade trajectories could be either repulsive or attractive (Van der Stigchel et al, 2006), and specifically demonstrated that saccade trajectories could deviate either toward a distracter or away from it depending on the time at which the distracter was shown (Theeuwes and Godijn, 2004; McSorley et al, 2006; Giuricich et al, 2023). This result recapitulates the idea discussed above but in the spatial domain: the exogenous effect of the distracter is, initially, to produce a motor plan toward it (attraction), but later on this plan is suppressed and a motor bias away from the distracter (repulsion) is observed instead.…”
Section: Discussionmentioning
confidence: 99%
“…If the brain decides to prioritize the initial target, the saccade might still show a curvature toward or away from the distractor, where the trajectory represents a vector sum of the activity evoked by the target and the distractor (Port and Wurtz, 2003). The temporal dynamics and direction of curvature depends on various factors (Van der Stigchel, 2010) such as target and distractor features (Kehoe et al, 2023), and the relative timing between the appearance of the distractor and initiation of the already planned saccade (Kehoe and Fallah, 2017; Giuricich et al, 2023). Several electrophysiological and inactivation studies have shown that saccade curvatures toward and away from distractors are correlated with higher excitation (McPeek et al, 2003; Port and Wurtz, 2003) and inhibition (Aizawa and Wurtz, 1998) in the SC neurons representing the distractor location.…”
Section: Introductionmentioning
confidence: 99%